Normative data of high‐resolution impedance manometry in the Chinese population. Issue 10 (23rd September 2013) - Shi, Yinan; Xiao, Yinglian; Peng, Sui; Lin, Jinkun; Xiong, Lishou; Chen, Minhu
Abstract Background and Aim Current normative data of high‐resolution manometry have been obtained from Western populations, and esophageal motility disorders have been categorized using Chicago classification. However, the utility of high‐resolution impedance manometry (HRiM) in the Chinese population has not been evaluated. The study aimed to investigate the normal reference of esophageal motility in healthy volunteers (as defined by Chicago classification) using HRiM. Methods Healthy, fasted volunteers underwent HRiM in a supine position with 10 liquid swallows and 10 viscous swallows. Integrated relaxation pressure (IRP), distal contractile integral (DCI), contractile front velocity (CFV), and distal latency were calculated. The interquartile ranges and the 95th percentile range for each metric were obtained. Results Forty‐two healthy volunteers were enrolled with 411 total liquid swallows and 398 viscous swallows available for analysis. A 20.5 mmHg of IRP and a 3195 mmHg·s·cm of DCI as the 95th percentile for liquid swallows were established. Using the reference range defined by Chicago classification, 6.3% (26/411) weak peristalsis and 0.7% (3/411) failed peristalsis for liquid swallows were observed; 12 (28.6%, 12/42) and 2 (4.7%, 2/42) individuals were diagnosed as esophagogastric junction outflow obstruction and weak peristalsis for liquid swallows. Compared with liquid swallows, viscous swallows had a decreased IRP (P = 0.000) and CFV (P = 0.000), and an unchanged DCI (P = 0.211). Conclusions HRiM normative data of both liquid and viscous swallows from healthy Chinese volunteers were established. The IRP and CFV were significantly decreased in the viscous swallows compared with those of the liquid swallows.